A New Fractal-Based Miniaturized Dual Band Patch Antenna for RF Energy Harvesting - Sika Shrestha; Seong Ro Lee; Dong-You Choi (International Journal of Antennas and Propagation)
The growth of wireless communications in recent years has made it necessary to develop compact, lightweight multiband antennas. Compact antennas can achieve the same performance as large antennas do with low price and with greater system integration. Dual-frequency microstrip antennas for transmission and reception represent promising approach for doubling the system capacity. In this work, a miniaturized dual band antenna operable at 2.45 and 5.8 GHz is constructed by modifying the standard microstrip patch antenna geometry into a fractal structure. In addition to miniaturization and dual band nature, the proposed antenna also removes unwanted harmonics without the use of additional filter component. Using a finite-element-method-based high frequency structure simulator (HFSS), the antenna is designed and its performance in terms of return loss, impedance matching, radiation pattern, and voltage standing wave ratio (VSWR) is demonstrated. Simulation results are shown to be in close agreement with performance measurements from an actual antenna fabricated on an FR4 substrate. The proposed antenna can be integrated with a rectifier circuit to develop a compact rectenna that can harvest RF energy in both of these frequency bands at a reduction in size of 25.98% relative to a conventional rectangular patch antenna.